Soluble CD40 ligand impairs the anti-platelet function of peripheral blood angiogenic outgrowth cells via increased production of reactive oxygen species - Khzam, Lara Bou; Hachem, Ahmed; Zaid, Younes; Boulahya, Rahma; Mourad, Walid; Merhi, Yahye (Thrombosis and Haemostasis, 2013)
Adult peripheral blood angiogenic early outgrowth cells (EOCs), also known as early endothelial progenitor cells, interact with other blood and vascular cells and may regulate atherothrombosis. We have previously shown that endothelial progenitor cells inhibit platelet function and thrombus formation. The CD40L/CD40 axis is a thrombo-inflammatory mediator that affects platelet and endothelial functions. It has been shown that EOCs express CD40, whereas platelets represent the major source of its soluble ligand (sCD40L), which impairs EOC function. We aimed to test the hypothesis that the sCD40L/CD40 axis affects the anti-platelet function of EOCs. Human peripheral blood mononuclear cell-derived EOCs in culture inhibited platelet aggregation. Pre-treatment of EOCs with sCD40L reduced their in-hibitory effect on platelet aggregation in a CD40-dependent manner. EOCs viability and release of the anti-aggregating agents, prostacyclin and nitric oxide, were not affected by sCD40L. However, production of reactive oxygen species (ROS) was increased in sCD40L–treated EOCs. Blockade of ROS reversed the effects of sCD40L–treated EOCs on platelet aggregation. This study reveals that the sCD40L/CD40 axis impairs the anti-platelet properties of EOCs through increased production of ROS. These data may explain the link between elevated levels of sCD40L, impaired activity of EOCs and enhanced platelet reactivity, and consequently the occurrence of atherothrombotic disease.
Keywords: CD40; CD40L; early outgrowth cells; platelets; reactive oxygen species